Environmental and cost analysis of carbon fibre composites recycling - Meng, Fanran (2017)
While carbon fibre reinforced plastic (CFRP) can reduce transportation energy use and greenhouse gas emissions by reducing vehicle weight, the production of virgin carbon fibre (CF) itself is energy intensive. CFRP recycling and the reutilisation of the recovered CF have the potential to compensate for the high impact of virgin CF production due to low cost and to open up new composites markets – e.g., in the automotive sector. The aim of the research is to examine the life cycle environmental and financial implications of a fluidised bed process to recycle CFRP wastes and to identify potential markets for CFRP reuse in automotive applications.